Efficient Straightforward Synthesis of Amidopiperazinophanes as Versatile Novel Supramolecular Scaffolds - Thirunarayanan, Ayyavu; Selvarani, Sivasamy; Francisco, Gracia; Rajakumar, Perumal (SynOpen, 2019)
A simple one-pot synthesis of amidopiperazinophanes with a combination of electron-deficient amide groups and electron-rich alkyne and piperazine functionalities has been achieved by using multicomponent reaction (MCR) methodology with the Mannich reaction. Herein, we demonstrate the synthesis of macrocyclic amide structures in good yields. These macrocycles, with electron donor/acceptor sites, are versatile molecules for host–guest and binding.
Keywords: supramolecular; piperazine; host-guest; amide; Mannich reaction; multicomponent reaction